Evaluation of a competitive inhibition ELISA based on the recombinant protein tSAG1 to detect anti–Neospora caninum antibodies in cattle - Novoa, María Belén; Valentini, Beatriz Susana; Torioni, Susana Marta; Primo, María Evangelina; Echaide, Ignacio Eduardo (American Association of Veterinary Laboratory Diagnosticians (AAVLD), 2022)
Neospora caninum is a protozoan parasite that causes abortion and important economic losses in cattle worldwide. There are no treatments or vaccines available; disease control is based on diagnosis and herd management strategies. We developed, validated, and evaluated under field conditions a competitive inhibition ELISA based on the truncated SAG1 protein (tSAG1), expressed in Escherichia coli, and the RafNeo5 monoclonal antibody (ciELISAtSAG1). A criterion based on the 3-y sequential serologic analysis of 230 dairy cows by IFAT was used as the gold standard. The assay was validated using 860 serum samples from cows that were consistently positive or negative by IFAT throughout the study period. ciELISAtSAG1 was then used to evaluate the prevalence of neosporosis in 16 beef cow herds (22 samples per herd, 352 total samples). The results were compared with those from IFAT and a commercial cELISA (cELISAVMRD). The ciELISAtSAG1 cutoff was ≥ 29%I, with a diagnostic sensitivity of 98.7% (95% CI = 96.8–99.7%) and a diagnostic specificity of 97.9% (95% CI = 96.4–99.0%). Concordance among IFAT, cELISAVMRD, and ciELISAtSAG1 was 90.3%. The agreement (κ) between ciELISAtSAG1 and the other 2 tests was ≥ 0.81. The overall prevalence of neosporosis in the 16 beef herds was 30% (range: 5–60%). The ciELISAtSAG1 could be useful for large-scale detection of anti–N. caninum antibodies in cattle and seroepidemiologic investigations, given its appropriate sensitivity and specificity, and the simplicity of production.